Conjoint Analysis to Determine the Perceptions of Restaurant Consumers in Choosing Halal-certified All-You-Can Eat Restaurants - Hadiantini, Ratih; Sarifiyono, Aggi Panigoro (KnE Social Sciences, 2024)
Halal certification is increasingly becoming a concern for Muslim consumers in choosing a place to eat, especially in restaurants with the concept of “all you can eat” (AYCE). This study aims to analyze the factors that influence consumer preferences. This research has important implications for the food and restaurant industry, especially for entrepreneurs who want to attract Muslim customers with “all you can eat” services that comply with halal principles. By understanding consumer preferences and the most influential attributes, restaurants can develop more effective strategies to meet consumer expectations and increase their competitiveness in an increasingly competitive market. The conjoint analysis method is used to identify the most important attributes for consumers in choosing AYCE restaurants in Bandung. The attributes analyzed include price, menu variety, cleanliness, location, and halal reputation. This research provides insight into how these factors interact in shaping consumer preferences and how restaurants can optimize their marketing strategies based on these findings. Keywords: all-you-can-eat, conjoint analysis, consumer preferences, halal-certified